The impact of audience response platform Mentimeter on the student and staff learning experience - Emma Mayhew; Madeleine Davies; Amanda Millmore; Lindsey Thompson; Alicia Pena Bizama (Association for Learning Technology, 2020)
Research suggests that active and discussion-driven dialogic approaches to teaching are more effective than passive learning methods. One way to encourage more participatory learning is through the adoption of simple and freely available audience response systems which allow instant and inclusive staff-student dialogue during teaching sessions. Existing literature is largely limited to exploring the impact of basic approaches to audience participation, using handheld cards or simple 'clickers'. Limited research exists looking at the impact and best use of a new generation of online audience response systems which have significantly expanded functionality. This article explores the impact of one of the most agile platforms, Mentimeter. It outlines impact on student satisfaction, enjoyment, voice and learning within small and large group settings across multiple disciplines drawing on 204 student survey responses. It also explores staff experiences and reflections on the key practical and pedagogical thinking required to optimise the use of this platform in higher education. The research responds to a need within the sector to react to rapid advances in teaching and learning technology, to provide evidence of impact for lecturers looking to improve student learning environments whilst being cognisant of the underlying pedagogy supportive of new practices.